Biological and Biochemical Roles of Two Distinct Cyclic Dimeric Adenosine 3′,5′-Monophosphate- Associated Phosphodiesterases in Streptococcus mutans - Konno, Hiroyasu; Yoshida, Yasuo; Nagano, Keiji; Takebe, Jun; Hasegawa, Yoshiaki (Frontiers in Microbiology, 2018)
Cyclic dimeric adenosine 3,5-monophosphate (c-di-AMP), a recently identified secondary messenger in bacteria, plays a role in several bacterial processes, including biofilm formation. It is enzymatically produced by diadenylate cyclase and cleaved by c-di-AMP phosphodiesterase. c-di-AMP is believed to be essential for the viability of bacterial cells that produce it. In the current study, the biochemical and biological roles of GdpP (SMU_2140c) and DhhP (SMU_1297), two distinct Streptococcus mutans phosphodiesterases involved in the pathway producing AMP from c-di-AMP, were investigated. Liquid chromatography-tandem mass spectrometry revealed that c-di-AMP was degraded to phosphoadenylyl adenosine (pApA) by truncated recombinant GdpP, and pApA was cleaved by recombinant DhhP to yield AMP. In-frame deletion mutants lacking the dhhP gene (dhhP) and both the gdpP and dhhP genes (gdpPdhhP) displayed significantly more biofilm formation than the wild-type and a mutant strain lacking the gdpP gene (gdpP; p <0.01). Furthermore, biofilm formation was restored to the level of the wild type strain upon complementation with dhhP. Optical and electron microscopy observations revealed that dhhP and gdpPdhhP mutants self-aggregated into large cell clumps, correlated with increased biofilm formation, but cell clumps were not observed in cultures of wild-type, gdpP, or strains complemented with gdpP and dhhP. Thus, deletion of dhhP presumably leads to the formation of bacterial cell aggregates and a subsequent increase in biofilm production.